Comparative study between open lumbopelvic fixation and percutaneous iliosacral fixation for management of sacral fractures - Abdelrahman Magdy Elhabashy; Ahmed Abdelaziz Fayed; Islam Sorour (Egyptian Journal of Neurosurgery, 2023)
Abstract Background The main aim of surgical intervention for unstable sacral fractures is to obtain a solid construct across the lumbopelvic junction to allow for early mobilization. Both iliosacral screw fixation (ISF) and lumbopelvic fixation (LPF) are widely used surgical techniques used for treatment of unstable sacral fractures. Nevertheless, it is unclear whether one technique provides more favorable postoperative outcomes than the other. Objective To compare the three-year outcome of ISF versus LPF in patients with unstable sacral fractures as regard effectiveness and safety of both techniques. Methods The study included 54 patients with sacral fractures who underwent sacral fusion using either ISF or LPF at a single institution. Patients were followed up for at least 3 years. Operative and postoperative data were collected and statistically calculated. Results Thirty patients were included in the ISF group and 24 patients in the LPF group. The operative time was notably higher in the LPF group (mean 107 min compared to 33 min in the ISF group; p = 0.002). Blood loss was also higher in the LPF group (mean 320 ml compared to 96 ml in the ISF; p = 0.004). Assessment of pelvic fusion was done via Majeed and Matta scores (pelvic fusion outcome scores). The ISF and LPF groups had a comparable Majeed score at the end of the third year of follow-up (excellent rate = 53.3% vs. 58.3%, respectively; p = 0.93). Likewise, ISF and LPF groups had comparable Matta score at the end of the third year of follow-up (excellent rate = 66.7% vs. 70.8%, respectively; p = 0.27). The most commonly reported postoperative complications in the ISF group were screw malposition in 2 cases out of 30 cases (6.6%) and non-union in 2 cases out of 30 cases (6.6%). On the other hand, the most commonly reported postoperative complications in the LPF group were implant prominence in 3 cases out of 24 cases (12.5%) and infection in 2 cases out of 24 cases (8.3%). Conclusion LPF and ISF have comparable safety and efficacy in patients with sacral fractures. ISF is an excellent and safe method of fixation, especially in old age to avoid open surgery-related complications. LPF is preferred in young active patients to benefit from rapid weight bearing after surgery and in cases with ambiguous sacral anatomy as sacral dysmorphism.